Rapid identification of Ebola virus and related filoviruses in fluid specimens using indirect immunoelectron microscopy. - Geisbert, T W (1991)
Recent filoviral outbreaks in animal primates have raised public awareness of the potential for filoviruses to become a public health concern; methods that efficiently identify these viruses are therefore of high priority. An indirect immunoelectron microscopy method, which uses homologous guinea pig polyclonal antiserum, successfully identified Ebola-related (Reston) virus particles in serum and tissue culture fluid specimens with infectivity titres of 300 plaque forming units (pfu) per ml or more. The sensitivity of this procedure is sufficient to show virus in most acute phase sera, and is equal to that of the antigen capture enzyme linked immunosorbent assay (ELISA). The immunoelectron microscopy fluid technique can differentiate among antigenically distinct filoviruses in less than three hours. It should be valuable in the rapid diagnosis of potential filoviral infections.